DETERMINTS OF INDONESIA'S EXPORTS TO BRICS COUNTRIES: A GRAVITY MODEL APPROACH - Rosid Efendi, Achmad Fadhor; Saleh, Mohammad; Hanim, Anifatul (International Journal of Research -GRANTHAALAYAH, 2025)
This study analyzes the determinants of Indonesia’s exports to BRICS countries (Brazil, Russia, India, China, and South Africa) using the gravity model approach. It examines the impact of GDP, geographical distance, exchange rates, and trade openness on exports from 2011 to 2023 using panel data regression with the Random Effects Model (REM). Data sources include ITC Trade Map, World Bank Open Data, and Exchange-Rates.org. The findings show that BRICS GDP positively and significantly influences Indonesia’s exports, indicating that higher economic growth in BRICS increases demand for Indonesian products. Distance has a negative and significant effect, confirming that greater transportation costs reduce trade. The exchange rate has a positive but insignificant impact, suggesting that currency depreciation can enhance exports but is not a dominant factor. Indonesia’s trade openness positively affects exports, while BRICS trade openness negatively influences them, implying that as BRICS countries liberalize trade, they may diversify import sources, reducing reliance on Indonesian goods. This research contributes to the literature by applying the gravity model with updated data and offers insights for policymakers and businesses on improving Indonesia’s trade relations with BRICS.